Jurisprudential Analysis on the Determination (Itsbat) of Marriage and the Potential Cancellation of Marriage for Illegal Guardianship (Case Study of the Marriage of Mahalini and Rizky Febian) - Nadia Arina Ilma (Universitas Wahid Hasyim Semarang, 2024)
Itsbat (determination) of marriage is a legal instrument to recognize marriages that are not recorded or do not meet the legal requirements under Islamic law. This research aims to analyze jurisprudence related to itsbat nikah and the potential for annulment of marriages involving illegitimate guardianship, with a case study of Mahalini and Rizky Febian’s marriage. The research uses normative juridical and empirical juridical approaches by examining legal documents such as the Compilation of Islamic Law (KHI), fiqh books, and court decisions. Secondary data was analyzed descriptively-qualitatively to describe legal facts and assess the consistency of legal application in similar cases. The results show that the appointment of a guardian without official authority violates Article 23 and Article 71 of the KHI, so it can be a basis for annulment of the marriage. In this case, although the nasab (descendant/family ties) guardian was ineligible due to religious differences, the appointment of an alternative guardian without legal legitimacy was also invalid. This research highlights the legal and social implications of the itsbat nikah decision, including its impact on the legal status of the couple and children. The novelty of the research lies in analyzing the relationship between the application of Islamic law, jurisprudence and community perceptions of public figures in the context of marriage law.